Haïti : la politique d’industrialisation par invitation - Robert Fatton Jr (Cahiers des Amériques Latines)
This article examines Haiti’s development strategy in the current decade, in the context of a changing political landscape. A number of critical dimensions are thus analyzed. They include the response to the 2010 earthquake, the links between the Haitian state and the international community, and the rocky road from the first to the second round of presidential elections held in 2010 and 2011. Particular attention is paid to the first half of the presidency of Michel Martelly and the direction it has set in terms of development priorities. The established international cooperation regime is discussed, as well as the « industrialization by invitation » strategy that has been put into place. Some alternative policy recommendations provide the concluding section.